2019
DOI: 10.1177/1745506519891302
|View full text |Cite
|
Sign up to set email alerts
|

Sufferings in silence: Violence against female workers in the ready-made garment industry in Bangladesh: A qualitative exploration

Abstract: Introduction: Despite the improved safety of the ready-made garment industry in Bangladesh since 2013, other workplace health and safety issues in the ready-made garment industry continue, especially violence towards female workers. This article examines this violence as well as the social norms and attitudes of key stakeholders underpinning it. Methods: Data were collected in four ready-made garment factories in Bangladesh through in-depth interviews, focus group discussions with female workers and key-inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 25 publications
3
33
1
Order By: Relevance
“…At this point, a garment factory owner mentioned about increased productivity during Ramadan when participants are fasting, since restroom minimized restroom usage. It showed an inherent tendency to neglect the basic physiological requirements of the participants as well as owners-this relates to the existing body of literature on the healthcare of garment workers (Akhter et al, 2019).…”
Section: Lack Of Concern Regarding Healthcarementioning
confidence: 94%
See 1 more Smart Citation
“…At this point, a garment factory owner mentioned about increased productivity during Ramadan when participants are fasting, since restroom minimized restroom usage. It showed an inherent tendency to neglect the basic physiological requirements of the participants as well as owners-this relates to the existing body of literature on the healthcare of garment workers (Akhter et al, 2019).…”
Section: Lack Of Concern Regarding Healthcarementioning
confidence: 94%
“…There have been improvements in the working environment in compliant garments, while others (non-compliant ones) have not. However, there are ongoing concerns raised in contemporary studies whether the lives of garment workers have improved or not (Akhter et al, 2019;Steinisch et al, 2013;Akhter, 2014). On the other hand, the garments workers' health-related issues are often neglected in the factories, where workers experience poor health facilities (Akhter et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The women glass bead makers are helpless in changing this discrimination against them and thus resort to silence. Previous studies on women working in the informal sector have reported that female workers who are influenced by culture-specific silence are mostly objects of poor working conditions such as poor remuneration, denial of essential allowances and working opportunities, and so on [ 31 ]. The findings of the study revealed that women glass bead makers experience similar poor working conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The culture-specific silence has led to the marginalization of women workers by their male counterparts in dominant positions at work [ 29 ]. Female workers who are entangled in the culture-specific silence, often face poor working conditions such as poor remuneration, withholding of salaries, verbal and physical abuse, denial of privileges, and other conditions of work [ 31 ]. Unfortunately, many of these female workers prefer remaining silent about their poor working conditions mostly because of the fear of losing their jobs [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…These two findings suggest bigger underlying problems in this sector: lack of worker participation and absence of trust even in worker welfare programs. Also, women workers were not making proportionate number of calls which mean very few reports of verbal abuse, verbal harassment, sexual abuse, and sexual harassment were coming to Helpline; however, previous studies clearly verified that women factory workers in developing countries face multitude of abuses and harassment 5‐8 . Training of workers on what should be reported is also essential.…”
Section: Discussionmentioning
confidence: 99%